2003
DOI: 10.1021/ef020135l
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of CO2, N2, and O2 on Natural Zeolites

Abstract: Pressure swing adsorption (PSA) and temperature swing adsorption are potential techniques for removing CO 2 from high-pressure fuel gas streams. Natural zeolites are suitable candidate sorbents for use in the PSA process. Studies of volumetric gas adsorption of CO 2 , N 2 , and O 2 on three natural zeolites, with different major cations, were conducted at 25 °C up to a pressure of 300 psi (2 × 10 6 Pa). Preferential adsorption of CO 2 was observed with all three zeolites. The natural zeolite with the highest s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
107
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(116 citation statements)
references
References 9 publications
3
107
0
Order By: Relevance
“…This trend can be observed in Table 4 (Bonenfant et al 2007;Kamiuto et al 2002;Li et al 2013;Yu et al 2012). The study of Siriwardane et al (2003) suggested that natural zeolites with the highest surface area and sodium (Na) content yield the highest adsorption capacity for CO 2 .…”
Section: Zeolites-based Adsorbentsmentioning
confidence: 73%
“…This trend can be observed in Table 4 (Bonenfant et al 2007;Kamiuto et al 2002;Li et al 2013;Yu et al 2012). The study of Siriwardane et al (2003) suggested that natural zeolites with the highest surface area and sodium (Na) content yield the highest adsorption capacity for CO 2 .…”
Section: Zeolites-based Adsorbentsmentioning
confidence: 73%
“…Zeolite 13X is recommended for CO 2 separation. Siriwardane et al (69) also reported that the zeolite with the highest sodium content gave the best separation of CO 2 from the gas mixtures.…”
Section: Process Descriptionmentioning
confidence: 94%
“…A wide variety of materials has been investigated as CO2 adsorbents, including metal oxides [9], activated carbons [10], zeolites [11,12], and metal-organic frame-works [13]. Alkali metal or alkaline earth metal oxides-based adsorbents have achieved high CO2 adsorption capacity [14].…”
Section: Introductionmentioning
confidence: 99%